'What vision?': experiences of Team members in a community service for adults with intellectual disabilities. Issue 3 (1st September 2016) - Clare, I. C. H.; Madden, E. M.; Holland, A. J.; Farrington, C. J. T.; Whitson, S.; Broughton, S.; Lillywhite, A.; Jones, E.; Wade, K. A.; Redley, M.; Wagner, A. P.
Abstract: Background: In the UK, the closure of 'long‐stay' hospitals was accompanied by the development of community teams (CTs) to support people with intellectual disabilities (IDs) to live in community settings. The self‐reported experiences of staff working in such teams have been neglected. Methods: Focusing on a single county‐wide service, comprising five multi‐disciplinary and inter‐agency CTs, we measured perceptions among the health care and care management Team members of (1) their personal well‐being; (2) the functioning of their team; and (3) the organisation's commitment to quality, and culture. Results: Almost three‐quarters of the questionnaires were returned (73/101; 72%). The scores of health care practitioners and care managers were very similar: (1) the MBI scores of more than half the respondents were 'of concern'; (2) similarly, almost four in ten respondents' scores on the Vision scale of the TCI were 'of concern'; (3) the perceived commitment to quality (QIIS‐II Part 2) was uncertain; and (4) the organisational culture (QIIS‐II, Part 1) was viewed as primarily hierarchical. Discussion: The perceived absence of a vision for the service, combined with a dominant culture viewed by its members as strongly focussed on bureaucracy and process, potentially compromises the ability of these CTs to respond proactively to the needs of people with IDs. Given the changes in legislation, policy and practice that have taken place since CTs were established, it would be timely to revisit their role and purpose.